2015
DOI: 10.3171/2014.11.jns1494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resident involvement in neurosurgery: an analysis of 8748 patients from the 2011 American College of Surgeons National Surgical Quality Improvement Program database

Abstract: OBJECT This study evaluates the impact of resident presence in the operating room on postoperative outcomes in neurosurgery. METHODS The authors retrospectively reviewed the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) and identified all cases treated in a neurosurgery service in 2011. Propensity scoring analysis and multiple logistic regression models were used to reduce patient bias and to assess independent effect of resident involvement. RESULTS Of the 8748 neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…3,4 Numerous studies were conducted to elucidate the relationship between resident involvement and postoperative complications with conflicting results. [5][6][7][8][9][10][11][12] Several studies have demonstrated that resident involvement was not a risk factor for increased complications in neurosurgery, orthopedic surgery, or urology. [5][6][7][8] Meanwhile, other studies have shown increased operative durations and post-operative complications when residents were involved in surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Numerous studies were conducted to elucidate the relationship between resident involvement and postoperative complications with conflicting results. [5][6][7][8][9][10][11][12] Several studies have demonstrated that resident involvement was not a risk factor for increased complications in neurosurgery, orthopedic surgery, or urology. [5][6][7][8] Meanwhile, other studies have shown increased operative durations and post-operative complications when residents were involved in surgery.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Several studies have demonstrated that resident involvement was not a risk factor for increased complications in neurosurgery, orthopedic surgery, or urology. [5][6][7][8] Meanwhile, other studies have shown increased operative durations and post-operative complications when residents were involved in surgery. [9][10][11][12] In ACDF, resident participation in the operating room occurs early on and continues through their senior years of training.…”
mentioning
confidence: 99%
“…In the absence of traditional high-level medical evidence (i.e., randomized controlled trials) for outcomes after many neurosurgical procedures, analysis of large prospective registries is becoming increasingly important in determining the exact risks and benefits of surgical intervention [16,18,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The data are collected by trained surgical reviewers employed at each participating site. The NSQIP dataset has been previously validated [18], and has been used to evaluate outcomes for a variety of neurosurgical procedures [15,16,[18][19][20][21][22][23][24][25][26].…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation